Analysis of the Influence of Investment in Education and Health on Economic Growth in Malaysia - Aqeela Noor Nadhirah; Tri Kurniawati; Zairenah Binti Md Nor (International Journal of Multidisciplinary Research of Higher Education, 2023)
This study aims to determine the effect of education as seen from the mean year of schooling and literacy rate, health as seen from life expectancy and infant mortality rate on economic growth in Malaysia. This study uses the panel regression analysis method to see the effect of the independent variables on the dependent variable as seen from data in 2016 to 2020 in Malaysia. By using the Classic Assumption Test and Multiple Linear Regression Analysis methods to see whether the independent variables can affect the dependent variable in Malaysia. The results of this study indicate that mean year of schooling, literacy rate, life expectancy and infant mortality rate have no significant effect on economic growth in Malaysia. From the research results, it is suggested to the government to be able to improve the quality of education and health in the community by providing facilities evenly throughout the country. The need to raise awareness that the importance of education and health as human capital investment. In addition, there is a need for good education and health planning in an effort to improve the quality of human resources.